Construction of A Model For The Implementation of Other Receivables Management at The Audit Board of the Republic of Indonesia - Zakaria, Muhammad Irvan; Saksono, R N Afsdy; Rahayu, Neneng Sri (Dinasti Publisher, 2025)
This study aims to analyse the factors causing the poor implementation of other receivables management by the BPK and to formulate a model for good management implementation at the BPK RI. The research method used is a qualitative approach and a case study at the BPK. Data collection was carried out through interviews and document review. The results of the study show that the BPK has not used the receivables module in the SAKTI application to manage other receivables, and that one-way communication has also been an obstacle. The BPK has good SOPs but does not yet have guidelines to support them. The recommended suggestions include forming a state receivables management team, providing effective communication training to staff involved in managing other receivables, and, last but not least, developing a State Receivables Management Guideline. This study recommends the adoption of an integrated internal control system model, namely the receivables management team as the first line, the Finance Bureau as the second line, and the Inspectorate General as the third line.